2023
DOI: 10.1038/s41467-023-37434-8
|View full text |Cite|
|
Sign up to set email alerts
|

Increasing extreme melt in northeast Greenland linked to foehn winds and atmospheric rivers

Abstract: The Greenland Ice Sheet has been losing mass at an increased rate in recent decades. In northeast Greenland, increasing surface melt has accompanied speed-ups in the outlet glaciers of the Northeast Greenland Ice Stream, which contain over one meter of sea level rise potential. Here we show that the most intense northeast Greenland melt events are driven by atmospheric rivers (ARs) affecting northwest Greenland that induce foehn winds in the northeast. Near low-elevation outlet glaciers, 80–100% of extreme (&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…The effect on sea ice north of 70°N is relatively subtle, where the total amount of significantly affected regions is smaller compared to SAT and PR (Figure 12, lower panel). Similar to the two‐sided AR‐TAS relation, sea ice melting can not only be triggered by heating from above, but can also initially occur due to increased ocean temperatures or strong winds, and then induce increased temperatures through evaporation, possibly strengthening ARs (Bintanja & Selten, 2014; Lei et al., 2018; Liang et al., 2023; Mattingly et al., 2023; P. Zhang et al., 2023). We find that especially ARs from Eurasia are associated with 20% lower SIC in the Kara Sea (Figure 12r).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The effect on sea ice north of 70°N is relatively subtle, where the total amount of significantly affected regions is smaller compared to SAT and PR (Figure 12, lower panel). Similar to the two‐sided AR‐TAS relation, sea ice melting can not only be triggered by heating from above, but can also initially occur due to increased ocean temperatures or strong winds, and then induce increased temperatures through evaporation, possibly strengthening ARs (Bintanja & Selten, 2014; Lei et al., 2018; Liang et al., 2023; Mattingly et al., 2023; P. Zhang et al., 2023). We find that especially ARs from Eurasia are associated with 20% lower SIC in the Kara Sea (Figure 12r).…”
Section: Resultsmentioning
confidence: 97%
“…Due to their potentially severe impacts on Arctic communities and ecosystems, there is large interest in determining the processes behind years of high AR occurrences and intensity. While in some regions ARs can be of benefit (e.g., by supplying water to dry areas in the mid‐latitudes), Arctic ARs are mainly associated with negative impacts: flooding of Arctic communities (Bachand & Walsh, 2022), melting of the Greenland Ice Sheet (GrIS) (Mattingly et al., 2018, 2023; Neff, 2018; Wang et al., 2020), sea ice loss (Gimeno et al., 2015; Hegyi & Taylor, 2018; Wang et al., 2020), or dust transport from the subtropics (D. Francis et al., 2018, 2022) which may further enhance melting through ice albedo changes. Mattingly et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Directionally consistent katabatic winds on the margins of the GIS and AIS, and föhn winds in the Antarctic Peninsula (AP) and northwestern Greenland, enhance surface melt rates (Datta et al., 2019; Laffin et al., 2021, 2022; Lenaerts et al., 2017; Mattingly et al., 2023; Wang et al., 2021). Katabatic winds originate in the cold, high, and dry ice sheet interior where relatively dense surface air drains downslope toward warmer regions.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of föhn and katabatic winds, which we will call downslope winds unless specified, on surface processes has been studied extensively on the AIS and through local case studies on the GIS. Observational and model studies have identified impacts of downslope winds on surface temperatures (Nylan et al., 2004; Parish and Bromwich, 1986), the surface energy budget (Kuipers Munneke et al., 2012, 2018; Laffin et al., 2021; Le Toumelin et al., 2021), surface mass balance including enhanced surface melt (Kuipers Munneke et al., 2012, 2018; Laffin et al., 2021; Mattingly et al., 2023; Wang et al., 2021), coastal precipitation (Grazioli et al., 2017), snow mass transport (Grazioli et al., 2017; Palm et al., 2017), ice shelf stability (Laffin et al., 2022), and sea ice and polynya formation with attendant impacts on ocean currents and biological productivity (Cape et al., 2014; Davis & Mcnider, 1997; Wenta & Cassano, 2020). Additionally, winds faster than 5–8 m/s can cause blowing snow that reflects shortwave radiation and enhances sublimation that limit surface melt (Grazioli et al., 2017; Le Toumelin et al., 2021), or expose bare ice that triggers the snow‐ice albedo feedback (Lenaerts et al., 2017).…”
Section: Introductionmentioning
confidence: 99%